2015
DOI: 10.1080/09512748.2015.1022592
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and adaptation: why even the Silicon Valley model is adapted as it diffuses to East Asia

Abstract: Diffusion scholarship expects little adaptation of core elements of policy models. However, the empirical reality is different; diffusion of even highly-regarded models, such as the Silicon Valley venture capital (VC) policy model, results in marked adaptation of the source model. This article asks: why does variance, rather than convergence, characterize the diffusion of the Silicon Valley VC model? The answer to this question lies in conceptualizing policymakers as rational in light of their normative contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
5
0
3
Order By: Relevance
“…A consistent group of critical scholars criticized the social impacts (Benner, 2003), labor divisions (Fuchs, 2014) and economic accumulation driven by "the Silicon Valley myth" warning about ongoing attempts to clone the Californian model around the world (Duff, 2016). While technical studies are still questioning whether the Silicon Valley model could be replicated in other areas (Cook & Joseph, 2001;Etzkowitz, 2011;Fung, Aminian & Tung, 2018;Henton & Held, 2013), empirical researches have already demonstrated that it has been already tested in East Asia (Klingler-Vidra, 2016); other scholars have also investigated the possibility to replicate the Silicon Valley model also in Europe (Aydalot & Keeble, 2018).…”
Section: State Of the Artmentioning
confidence: 99%
“…A consistent group of critical scholars criticized the social impacts (Benner, 2003), labor divisions (Fuchs, 2014) and economic accumulation driven by "the Silicon Valley myth" warning about ongoing attempts to clone the Californian model around the world (Duff, 2016). While technical studies are still questioning whether the Silicon Valley model could be replicated in other areas (Cook & Joseph, 2001;Etzkowitz, 2011;Fung, Aminian & Tung, 2018;Henton & Held, 2013), empirical researches have already demonstrated that it has been already tested in East Asia (Klingler-Vidra, 2016); other scholars have also investigated the possibility to replicate the Silicon Valley model also in Europe (Aydalot & Keeble, 2018).…”
Section: State Of the Artmentioning
confidence: 99%
“…Pero entre uno y otros pueden mediar también factores ideacionales. Este punto ha sido formulado recientemente por Klingler-Vidra (2015). Según ella, la «racionalidad contextual» puede jugar un papel fundamental transformando significativamente el modelo original 5 .…”
Section: El Papel De Las Ideas En La Adopción Y Adaptación De Modelosunclassified
“…Desde luego, la teoría de difusión admite que existen procesos locales de adaptación (Weyland, 2007: 58-66). Durante los últimos años, nuevas investigaciones de corte empírico han insistido en que las diferencias entre las sucesivas copias pueden, incluso, ser muy significativas (Klingler-Vidra, 2015).…”
Section: ¿Cómo Reconocer Y Explicar Procesos De Difusión?unclassified
See 1 more Smart Citation
“…During the past four decades, over forty countries have implemented policy attempting to create local VC industries (Brander et al 2014;Klingler-Vidra 2015;Wright et al 2005). Partly stemming from these policy attempts, VC has spread widely, as has the limited partnership as an organisational form (Aizenman and Kendall 2008;Guler and Guillen 2010;Mayer et al 2005;Megginson 2004).…”
Section: Introductionmentioning
confidence: 99%